(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Anemia and hyperhomocysteinemia are risk factor of mortality of patients on dialysis. This study was conducted to assess the relationship of hemoglobin and homocysteine levels and mortality of patients on hemodialysis. Materials and Methods. Fifty patients on hemodialysis and 20 healthy individuals were enrolled in the study. Blood samples were drawn for measurement of hematological parameters, serum iron, serum ferritin, transferrin saturation, and homocysteine levels. The patients were followed up for 1 year to determine the mortality rate and evaluate its association with anemia and hyperhomocysteinemia. Results. The majority the patients (54%) were not on erythropoietin therapy. Forty-three patients (86%) were anemic (hemoglobin < 11 g/dL). Serum ferritin was high (> 500 ng/mL) in 33 patients (66%). Mortality was 28% in 1 year (33% in anemic patients versus no death among patients with a hemoglobin level greater than 11 g/dL). The relative risk of mortality was increased by 1.58 with every 1 g/dL decrease in hemoglobin level. All of the patients had a high homocysteine level, and a significant difference was observed between the homocysteine levels of the patients on hemodialysis and the control group (P < .001). Hyperhomocysteinemia did not affect mortality. In multivariate Cox regression analysis, only hemoglobin level was associated with mortality. Conclusions. Almost all of our patients on hemodialysis were anemic and this condition was a risk factor of mortality. Iron stores, however, were adequate in more than half of the patients. The reason of anemia could be untreated erythropoietin deficiency. Hyperhomocysteinemia was present in the majority of the patients, but it did not independently affect mortality.